Defining ukuthwasa as a pedagogy: an autoethnographic exploration into the knowledge acquisition process of ukuthwasa at a training school(lefehlo) in Soweto, Johannesburg - Mokgethi, Lebogang Esme (My University, 2018)
The Apartheid Era in South Africa was not only a period of oppression of the indigenous people of South Africa; it was also a system that prohibited the right to practice indigenous customs and rituals that were in existence before the colonisation of the country. One of the practices that were prohibited and even deemed as witchcraft is that of training to become a traditional healer otherwise known as ukuthwasa. Ukuthwasa is defined as the active learning and training process undertaken by those who have an ancestral calling to become traditional health practitioners. Today, ukuthwasa is still clouded by mystery, superstition and the stigmatic notions of witchcraft. In the dawn of decolonization, various academics have taken to the fore to document not just ukuthwasa, but the holistic role of a traditional health practitioner (THP). Recent research has defined ukuthwasa as a process of identity formation, rituals and as a learning experience. With the strides that have been made in redefining ukuthwasa, there has been minimal information highlighting the role of indigenous knowledge systems involved in the process. As one with the calling to become a THP, using the ethnographic data obtained from my personal journey of ukuthwasa, as well as that of 2 other initiates and the trainer, one discovered that the process of ukuthwasa is an educational journey with its own competencies and training methodologies. Furthermore the research revealed that ukuthwasa is a developmental process that creates an environment of training and learning specifically for the critical consciousness development of the initiates. It is then outlined that through dreams, visual and audio material as well as the relationship between the initiate and the trainer, ukuthwasa is defined as a critical pedagogy that capacitates the initiate with knowledge and skills that will allow the individual to become a positive influence in society.
A thesis submitted in partial fulfillment of the requirements for the Masters of Arts Degree in Anthropology under the Humanities Faculty of the University of the Witwatersrand, Johannesburg 2018